FAKTOR-FAKTOR YANG MAMPU MEMPENGARUHI MOTIVASI KERJA PADA KARYAWAN KANTOR NOTARIS - Dhita Hafizha Asri; Agnes Fitrian (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of this study was to analyze the factors that influence the work motivation of employees who work in notary offices in Batam City. The sample used in this study was 151 people, and 151 were also respondents. In this research, five variables were used to test whether these five variables had an effect on the work motivation of employees who work in the notary's office. The five variables are work culture, rewards, compensation, punishment and training. And of these five variables, the results of research using the Smart PLS analysis tool provide the answer that the variable that has no significant effect on work motivation is the punishment variable.